Mechanism of conditional partner selectivity in MITF/TFE family transcription factors with a conserved coiled coil stammer motif. Issue 2 (28th November 2019) - Pogenberg, Vivian; Ballesteros-Álvarez, Josué; Schober, Romana; Sigvaldadóttir, Ingibjörg; Obarska-Kosinska, Agnieszka; Milewski, Morlin; Schindl, Rainer; Ögmundsdóttir, Margrét Helga; Steingrímsson, Eiríkur; Wilmanns, Matthias
Abstract: Interrupted dimeric coiled coil segments are found in a broad range of proteins and generally confer selective functional properties such as binding to specific ligands. However, there is only one documented case of a basic-helix–loop–helix leucine zipper transcription factor—microphthalmia-associated transcription factor (MITF)—in which an insertion of a three-residue stammer serves as a determinant of conditional partner selectivity. To unravel the molecular principles of this selectivity, we have analyzed the high-resolution structures of stammer-containing MITF and an engineered stammer-less MITF variant, which comprises an uninterrupted symmetric coiled coil. Despite this fundamental difference, both MITF structures reveal identical flanking in-phase coiled coil arrangements, gained by helical over-winding and local asymmetry in wild-type MITF across the stammer region. These conserved structural properties allow the maintenance of a proper functional readout in terms of nuclear localization and binding to specific DNA-response motifs regardless of the presence of the stammer. By contrast, MITF heterodimer formation with other bHLH-Zip transcription factors is only permissive when both factors contain either the same type of inserted stammer or no insert. Our data illustrate a unique principle of conditional partner selectivity within the wide arsenal of transcription factors with specific partner-dependent functional readouts.